A high dielectric constant polyimide film and a method for preparing the same

CN122668412APending Publication Date: 2026-09-01DATONG CO POLYMER (XIAN) TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611050298.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

聚酰亚胺(PI)因其优异的耐热性和良好的力学性能,成为极具潜力的高温储能介质候选材料,但其本征介电常数偏低且高温下损耗急剧上升,难以满足高能量密度和小型化的需求

Benefits of technology

1、本发明以高介电钛酸钡为核,包覆宽带隙氧化铝壳,制得BT@Al2O3复合填料;既保留核的高极化特性,显著提升了复合薄膜的介电常数,又通过壳层抑制漏电流,降低介电损耗,从而在提高介电常数的同时保证了材料的击穿强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of polyimide film, in particular to a polyimide film with high dielectric constant and a preparation method thereof.The present application uniformly stirs aluminum isopropoxide and ethylene glycol, sequentially adds acetylacetone and acetic acid to form an alumina transparent sol;ball-mills the barium titanate with the alumina sol, sieves, and performs heat treatment to obtain BT@Al2O3;under the protection of nitrogen, dissolves 3,3',4,4'-diphenyl tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride and 4,4'-bis(3-aminophenoxy)diphenyl sulfone in N,N-dimethylformamide, and after reaction, a polyamic acid solution is prepared;the BT@Al2O3 and modified boron nitride nanosheet are added into the polyamic acid solution, sheared and ultrasonically dispersed to prepare a composite slurry;the composite slurry is cast into a film, solidified, naturally cooled, and a polyimide film is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyimide film technology, specifically to a high dielectric constant polyimide film and its preparation method. Background Technology

[0002] With the rapid development of emerging fields such as new energy vehicles, photovoltaic inverters, consumer electronics, and 5G communications, higher performance requirements are being placed on electronic components such as thin-film capacitors. There is an urgent need to develop novel dielectric materials that combine high dielectric constant, low loss, high breakdown strength, and excellent high-temperature stability. Polyimide (PI) has become a highly promising candidate material for high-temperature energy storage due to its excellent heat resistance and good mechanical properties. However, its intrinsic dielectric constant is relatively low, and its loss increases sharply at high temperatures, making it difficult to meet the demands for high energy density and miniaturization.

[0003] Existing modification technologies face three major bottlenecks: First, the industry often improves the dielectric constant by adding high-dielectric ceramic fillers (such as barium titanate), but these fillers require high loading amounts to achieve high dielectric constants, leading to a decrease in the tensile strength of the material. Furthermore, dielectric mismatch and interfacial incompatibility exist between the filler and the polymer matrix, which not only reduces breakdown strength and insulation performance but also increases processing difficulty, making it difficult to fabricate large-area uniform films. Second, although conductive fillers (such as rGO) can further improve the dielectric constant, excessive use can easily induce leakage current, leading to increased dielectric loss. Finally, the fabrication process of multilayer thin films is complex and has high industrialization costs.

[0004] Therefore, we propose a polyimide film with high dielectric constant and its preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide a polyimide film with a high dielectric constant and a method for preparing the same, so as to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a polyimide film with high dielectric constant includes the following steps: Step S1: Aluminum isopropoxide and ethylene glycol are stirred evenly, and acetylacetone and acetic acid are added sequentially to form a transparent alumina sol; barium titanate and alumina sol are ball-milled, sieved, and heat-treated to obtain BT@Al2O3; Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone are dissolved in N,N-dimethylformamide. After the reaction, a polyamic acid solution is obtained. Step S3: Add BT@Al2O3 and modified boron nitride nanosheets to a polyamic acid solution, and disperse by shearing and ultrasonication to obtain a composite slurry; Step S4: Cast the composite slurry into a film, cure it, and allow it to cool naturally to obtain a polyimide film.

[0007] In a more optimized scheme, in step S1, the mass ratio of aluminum isopropoxide, ethylene glycol, acetylacetone and acetic acid is 1:(8-12):(0.3-0.6):(0.4-0.8).

[0008] In a more optimized scheme, in step S1, the mass ratio of barium titanate to alumina sol is 1:(50-100).

[0009] In a more optimized scheme, the ball milling is carried out in anhydrous ethanol medium for 4-6 hours, and the drying temperature is 80℃.

[0010] In a more optimized scheme, the heat treatment temperature is 600-620℃ and the holding time is 1.5-2.0h.

[0011] In a more optimized scheme, in step S2, the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone is (1-3):(2-3):(4-5).

[0012] In a more optimized scheme, the reaction process conditions in step S2 are: reacting at 25-35℃ for 3-5 hours.

[0013] In a more optimized scheme, the solid content of the polyamic acid solution in step S2 is 15 wt%.

[0014] In a more optimized scheme, in step S3, the composite slurry includes the following raw materials: by weight, 15-30 parts BT@Al2O3, 1-5 parts modified boron nitride nanosheets, and 65-85 parts polyamic acid solution.

[0015] A more optimized approach is to prepare the modified boron nitride nanosheets as follows: Step A: Adjust the pH of the Tris-HCl buffer solution to 8.5, add dopamine hydrochloride and mix well to obtain a dopamine solution; add boron nitride nanosheets to the dopamine solution, stir at 50-60℃ for 12-24h, and after filtration, washing and drying, obtain polydopamine-modified boron nitride nanosheets. Step B: Mix hydroxyl-terminated fluorinated vinyl polysiloxane, mercaptopropyl isobutylated cage-like silsesquioxane, 2,2-dimethoxyphenylacetophenone and toluene evenly, react under 300-500W ultraviolet light for 10-20 min, and obtain fluorinated POSS after centrifugation, washing and drying; Step C: Polydopamine-modified boron nitride nanosheets are ultrasonically dispersed in toluene, fluorinated POSS is added, and the mixture is stirred at 60-70℃ for 10-14 hours. After filtration, washing, and drying, modified boron nitride nanosheets are obtained.

[0016] In a more optimized scheme, in step A, the concentration of Tris-HCl buffer is 0.01 mol / L, the concentration of dopamine solution is 3-5 g / L, and the mass of boron nitride nanosheets is 1-3% of the mass of Tris-HCl buffer.

[0017] A more optimized scheme is that the fluorinated POSS comprises the following raw materials: by weight, 5-10 parts of hydroxyl-terminated fluorinated vinyl polysiloxane, 1-5 parts of mercaptopropyl isobutylated cage-like silsesquioxane, 0.1-0.5 parts of 2,2-dimethoxyphenyl acetophenone, and 10-20 parts of toluene.

[0018] A more optimized method for preparing the hydroxyl-terminated fluorinated vinyl polysiloxane is as follows: Under nitrogen protection, octamethylcyclotetrasiloxane, pentamethylpentylcyclopentasiloxane, and trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 100-110°C, tetramethylammonium hydroxide and deionized water are added and mixed evenly, and the reaction is carried out for 3-5 hours. The temperature is then further increased to 145-150°C and held for 2-3 hours. After filtration and drying, the hydroxyl-terminated fluorinated vinyl polysiloxane is obtained.

[0019] In a more optimized scheme, the mass ratio of octamethylcyclotetrasiloxane, pentamethylpentylcyclopentasiloxane, and trifluoropropyltrimethylcyclotrisiloxane is 1:(1.0-1.2):(2.0-2.2).

[0020] In a more optimized scheme, the mass of the tetramethylammonium hydroxide is 0.03-0.05% of the mass of trifluoropropyltrimethylcyclotrisiloxane, and the mass of the deionized water is 0.1-0.3% of the mass of trifluoropropyltrimethylcyclotrisiloxane.

[0021] In a more optimized scheme, in step C, the mass ratio of polydopamine-modified boron nitride nanosheets, toluene, and fluorinated POSS is 1:(10-12):(2-3).

[0022] In a more optimized scheme, the specific curing process in step S4 is as follows: gradient curing at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h.

[0023] In a more optimized scheme, the thickness of the polyimide film is 20-50 μm.

[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses high-dielectric barium titanate as the core and coats it with a wide-bandgap alumina shell to prepare BT@Al2O3 composite filler. It retains the high polarization characteristics of the core, significantly improves the dielectric constant of the composite film, and suppresses leakage current and reduces dielectric loss through the shell, thereby ensuring the breakdown strength of the material while improving the dielectric constant.

[0025] 2. This invention first utilizes the self-polymerization properties of dopamine to coat a polydopamine layer onto the surface of boron nitride nanosheets, thus preparing polydopamine-modified boron nitride nanosheets, effectively improving the surface activity of BNNS. Simultaneously, using deionized water as a capping agent and tetramethylammonium hydroxide as a catalyst, this invention prepares hydroxyl-terminated fluorinated vinyl polysiloxanes with high viscosity and excellent hydrophobic properties through the reaction of octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane, and pentamethylpentavinylcyclopentasiloxane. Then, the hydroxyl-terminated fluorinated vinyl polysiloxane undergoes a mercapto-olefinic click reaction with mercaptopropylisobutylated cage-like silsesquioxane to introduce fluorinated segments into the cage-like structure of the POSS, thus preparing fluorinated POSS. Finally, the fluorinated POSS is grafted onto the surface of polydopamine-modified boron nitride nanosheets to obtain modified boron nitride nanosheets. On the one hand, introducing the inherent hollow cage structure and low dielectric constant of POSS into the system is beneficial for adjusting the dielectric properties of the composite material. On the other hand, the fluorinated segments can reduce the surface energy of the filler surface, significantly enhance the interfacial compatibility between the filler and the polyimide matrix, thereby effectively inhibiting the agglomeration of the filler and improving the mechanical properties and thermal stability of the film.

[0026] 3. This invention introduces modified boron nitride nanosheets and BT@Al2O3 composite filler into a polyimide matrix to construct a dual-filler synergistic network. BT@Al2O3 provides a high polarization response; while the two-dimensional sheet-like structure of BNNS forms a physical barrier network in the matrix, effectively extending the breakdown path of electrical trees and increasing the breakdown field strength of the composite film. Furthermore, it complements the structure of BT@Al2O3, achieving a simultaneous improvement in dielectric constant and breakdown strength. The synergistic effect of the two fillers enables the polyimide film prepared by this invention to maintain a high dielectric constant while also possessing high breakdown strength, low dielectric loss, and good mechanical properties, resulting in excellent overall performance. Detailed Implementation

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Unless otherwise specified, all the following quantities are by weight. It should be noted that there are no special restrictions on the purchasers of any of the raw materials involved in this invention. Exemplary examples include (in this embodiment): barium titanate: particle size 100nm; boron nitride nanosheets: sheet size 1-2μm, thickness 4-10nm; mercaptopropyl isobutylated cage-like silsesquioxane: purchased from Xi'an Qiyue Biotechnology Co., Ltd.; the remaining raw materials are commercially available.

[0029] Example 1: A method for preparing a polyimide film with high dielectric constant, comprising the following processes: Step S1: 60 parts of aluminum isopropoxide and 720 parts of ethylene glycol are stirred evenly at 80°C, and 18 parts of acetylacetone and 24 parts of acetic acid are added sequentially to form a transparent alumina sol; 15 parts of barium titanate and 750 parts of alumina sol are ball-milled in anhydrous ethanol medium for 4 hours, dried at 80°C, passed through an 80-mesh steel sieve, and heat-treated in air at 600°C for 1.5 hours to obtain BT@Al2O3; Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 25°C for 3 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 1:2:4. Step S3: Add 15 parts of BT@Al2O3 and 1 part of modified boron nitride nanosheets to 65 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S4: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and allow it to cool naturally to obtain a polyimide film; The preparation method of modified boron nitride nanosheets is as follows: Step A: Adjust the pH of 100 parts of 0.01mol / L Tris-HCl buffer solution to 8.5, add dopamine hydrochloride and mix well to obtain a 3g / L dopamine solution; add 1 part of boron nitride nanosheets to the dopamine solution, stir at 50℃ for 12h, and after filtration, washing and drying, obtain polydopamine modified boron nitride nanosheets. Step B: Mix 5 parts of hydroxyl-terminated fluorinated vinyl polysiloxane, 1 part of mercaptopropyl isobutylated cage-like silsesquioxane, 0.1 parts of 2,2-dimethoxyphenylacetophenone, and 10 parts of toluene evenly, react under 300W ultraviolet light for 10 min, and obtain fluorinated POSS after centrifugation, washing, and drying. Step C: Disperse 1 part of polydopamine-modified boron nitride nanosheets ultrasonically in 10 parts of toluene, add 2 parts of fluorinated POSS, stir at 60°C for 10 h, and after filtration, washing and drying, obtain modified boron nitride nanosheets. The preparation method of hydroxyl-terminated fluorinated vinyl polysiloxane is as follows: Under nitrogen protection, 5 parts of octamethylcyclotetrasiloxane, 5 parts of pentamethylpentylcyclopentasiloxane and 10 parts of trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 100°C, 0.0015 parts of tetramethylammonium hydroxide and 0.005 parts of deionized water are added and mixed evenly, reacted for 3 hours, and then heated to 145°C and kept at that temperature for 2 hours. After filtration and drying, hydroxyl-terminated fluorinated vinyl polysiloxane is obtained.

[0030] Example 2: A method for preparing a polyimide film with high dielectric constant, comprising the following processes: Step S1: 160 parts of aluminum isopropoxide and 1600 parts of ethylene glycol are stirred evenly at 80°C. Then, 80 parts of acetylacetone and 96 parts of acetic acid are added sequentially to form a transparent alumina sol. 20 parts of barium titanate and 1600 parts of alumina sol are ball-milled in anhydrous ethanol medium for 5 hours. The mixture is dried at 80°C, passed through an 80-mesh steel sieve, and heat-treated in air at 610°C for 1.8 hours to obtain BT@Al2O3. Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 30°C for 4 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 2:2.5:4.5. Step S3: Add 20 parts of BT@Al2O3 and 3 parts of modified boron nitride nanosheets to 75 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S4: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and allow it to cool naturally to obtain a polyimide film; The preparation method of modified boron nitride nanosheets is as follows: Step A: Adjust the pH of 150 parts of 0.01mol / L Tris-HCl buffer solution to 8.5, add dopamine hydrochloride and mix well to obtain a 4g / L dopamine solution; add 3 parts of boron nitride nanosheets to the dopamine solution, stir at 55℃ for 20h, and after filtration, washing and drying, obtain polydopamine modified boron nitride nanosheets. Step B: Mix 8 parts of hydroxyl-terminated fluorinated vinyl polysiloxane, 3 parts of mercaptopropyl isobutylated cage-like silsesquioxane, 0.3 parts of 2,2-dimethoxyphenylacetophenone, and 15 parts of toluene evenly, react under 400W ultraviolet light for 15 min, and obtain fluorinated POSS after centrifugation, washing, and drying. Step C: Disperse 3 parts of polydopamine-modified boron nitride nanosheets ultrasonically in 33 parts of toluene, add 7.5 parts of fluorinated POSS, stir at 65°C for 12 hours, and after filtration, washing and drying, obtain modified boron nitride nanosheets. The preparation method of hydroxyl-terminated fluorinated vinyl polysiloxane is as follows: Under nitrogen protection, 4 parts of octamethylcyclotetrasiloxane, 4.4 parts of pentamethylpentylcyclopentasiloxane and 8.4 parts of trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 105℃, 0.0016 parts of tetramethylammonium hydroxide and 0.008 parts of deionized water are added and mixed evenly, reacted for 4 hours, and then heated to 148℃ and kept at that temperature for 2.5 hours. After filtration and drying, hydroxyl-terminated fluorinated vinyl polysiloxane is obtained.

[0031] Example 3: A method for preparing a polyimide film with high dielectric constant, comprising the following processes: Step S1: 250 parts of aluminum isopropoxide and 3000 parts of ethylene glycol are stirred evenly at 80°C. Then, 150 parts of acetylacetone and 200 parts of acetic acid are added sequentially to form a transparent alumina sol. 30 parts of barium titanate and 3000 parts of alumina sol are ball-milled in anhydrous ethanol medium for 6 hours. The mixture is dried at 80°C, passed through an 80-mesh steel sieve, and heat-treated in air at 620°C for 2 hours to obtain BT@Al2O3. Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 35°C for 5 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 3:3:5. Step S3: Add 30 parts of BT@Al2O3 and 5 parts of modified boron nitride nanosheets to 85 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S4: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and allow it to cool naturally to obtain a polyimide film; The preparation method of modified boron nitride nanosheets is as follows: Step A: Adjust the pH of 200 parts of 0.01 mol / L Tris-HCl buffer solution to 8.5, add dopamine hydrochloride and mix well to obtain a 5 g / L dopamine solution; add 6 parts of boron nitride nanosheets to the dopamine solution, stir at 60℃ for 24 h, and after filtration, washing and drying, obtain polydopamine modified boron nitride nanosheets. Step B: Mix 10 parts of hydroxyl-terminated fluorinated vinyl polysiloxane, 5 parts of mercaptopropyl isobutylated cage-like silsesquioxane, 0.5 parts of 2,2-dimethoxyphenyl acetophenone and 20 parts of toluene evenly, react under 500W ultraviolet light for 20 min, and obtain fluorinated POSS after centrifugation, washing and drying. Step C: Disperse 5 parts of polydopamine-modified boron nitride nanosheets ultrasonically in 60 parts of toluene, add 15 parts of fluorinated POSS, stir at 70°C for 14 hours, and after filtration, washing and drying, obtain modified boron nitride nanosheets. The preparation method of hydroxyl-terminated fluorinated vinyl polysiloxane is as follows: Under nitrogen protection, 5 parts of octamethylcyclotetrasiloxane, 6 parts of pentamethylpentylcyclopentasiloxane and 11 parts of trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 110°C, 0.0025 parts of tetramethylammonium hydroxide and 0.015 parts of deionized water are added and mixed evenly, reacted for 5 hours, and then heated to 150°C and kept at that temperature for 3 hours. After filtration and drying, hydroxyl-terminated fluorinated vinyl polysiloxane is obtained.

[0032] Comparative Example 1: Comparative Example 1 is based on Example 2, but modified boron nitride nanosheets were not introduced in Comparative Example 1. The remaining process steps and reaction parameters are the same as in Example 2; the specific differences are as follows: A method for preparing a polyimide film with high dielectric constant includes the following processes: Step S1: 160 parts of aluminum isopropoxide and 1600 parts of ethylene glycol are stirred evenly at 80°C. Then, 80 parts of acetylacetone and 96 parts of acetic acid are added sequentially to form a transparent alumina sol. 20 parts of barium titanate and 1600 parts of alumina sol are ball-milled in anhydrous ethanol medium for 5 hours. The mixture is dried at 80°C, passed through an 80-mesh steel sieve, and heat-treated in air at 610°C for 1.8 hours to obtain BT@Al2O3. Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 30°C for 4 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 2:2.5:4.5. Step S3: Add 20 parts of BT@Al2O3 to 75 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S4: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and then cool it naturally to obtain a polyimide film.

[0033] Comparative Example 2: Comparative Example 2 is based on Example 2, except that BT@Al2O3 is replaced with the same mass of barium titanate, and the remaining process steps and reaction parameters are the same as in Example 2; the specific differences are as follows: A method for preparing a polyimide film with high dielectric constant includes the following processes: Step S1: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 30°C for 4 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 2:2.5:4.5. Step S2: Add 20 parts of barium titanate and 3 parts of modified boron nitride nanosheets to 75 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S3: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and then cool it naturally to obtain a polyimide film.

[0034] Comparative Example 3: Comparative Example 3 is based on Example 2. The filler was not modified in Comparative Example 3; instead, BT@Al2O3 was replaced with the same mass of barium titanate, and the modified boron nitride nanosheets were replaced with the same mass of boron nitride nanosheets. The remaining process steps and reaction parameters were the same as in Example 2. Specific differences are as follows: A method for preparing a polyimide film with high dielectric constant includes the following processes: Step S1: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 30°C for 4 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 2:2.5:4.5. Step S2: Add 20 parts of barium titanate and 3 parts of boron nitride nanosheets to 75 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S3: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and then cool it naturally to obtain a polyimide film.

[0035] Comparative Example 4: Comparative Example 4 is based on Example 2, but 3,3',4,4'-benzophenone tetracarboxylic dianhydride was not introduced; the remaining process steps and reaction parameters are the same as in Example 2; the specific differences are as follows: A method for preparing a polyimide film with high dielectric constant includes the following processes: Step S1: 160 parts of aluminum isopropoxide and 1600 parts of ethylene glycol are stirred evenly at 80°C. Then, 80 parts of acetylacetone and 96 parts of acetic acid are added sequentially to form a transparent alumina sol. 20 parts of barium titanate and 1600 parts of alumina sol are ball-milled in anhydrous ethanol medium for 5 hours. The mixture is dried at 80°C, passed through an 80-mesh steel sieve, and heat-treated in air at 610°C for 1.8 hours to obtain BT@Al2O3. Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-bis(3-aminophenoxy)diphenyl sulfone were dissolved in N,N-dimethylformamide and reacted at 30°C for 4 hours to obtain a polyamic acid solution with a solid content of 15 wt%; the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-bis(3-aminophenoxy)diphenyl sulfone was 2:4.5. Step S3: Add 20 parts of BT@Al2O3 and 3 parts of modified boron nitride nanosheets to 75 parts of polyamic acid solution, and then perform high-speed shearing at 15000 rpm for 20 min and ultrasonic dispersion for 30 min to obtain composite slurry; Step S4: Cast the composite slurry into a film, cure it in a gradient at 80℃ / 2h, 150℃ / 1h, 250℃ / 1h, and 300℃ / 0.5h, and then cool it naturally to obtain a polyimide film.

[0036] Experiment: Polyimide films obtained in Examples 1-3 and Comparative Examples 1-4 were used to prepare samples. Their properties were tested and the test results were recorded. The dielectric constant and dielectric loss of the sample were tested using a microwave network analyzer at 25℃ and 150Hz. The breakdown voltage of the sample was tested using a voltage breakdown tester with DC current and a voltage boost rate of 0.1kV / s. The mechanical properties of the sample were tested using a universal testing machine with a sample size of 25mm×5mm and a tensile speed of 2mm / min.

[0037] The test results are shown in Table 1.

[0038] Table 1. Performance test results of polyimide films

[0039] Based on the data in the table above, the following conclusions can be clearly drawn: The polyimide film prepared by this invention not only has excellent mechanical properties, but also excellent dielectric properties.

[0040] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a polyimide film with high dielectric constant, characterized in that: Includes the following steps: Step S1: Aluminum isopropoxide and ethylene glycol are stirred evenly, and acetylacetone and acetic acid are added sequentially to form a transparent alumina sol; barium titanate and alumina sol are ball-milled, sieved, and heat-treated to obtain BT@Al2O3; Step S2: Under nitrogen protection, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone are dissolved in N,N-dimethylformamide. After the reaction, a polyamic acid solution is obtained. Step S3: Add BT@Al2O3 and modified boron nitride nanosheets to a polyamic acid solution, and disperse by shearing and ultrasonication to obtain a composite slurry; Step S4: Cast the composite slurry into a film, cure it, and allow it to cool naturally to obtain a polyimide film.

2. The method for preparing a high dielectric constant polyimide film according to claim 1, characterized in that... In step S1, the mass ratio of aluminum isopropoxide, ethylene glycol, acetylacetone, and acetic acid is 1:(8-12):(0.3-0.6):(0.4-0.8).

3. The method for preparing a high dielectric constant polyimide film according to claim 1, characterized in that: The heat treatment temperature is 600-620℃, and the holding time is 1.5-2.0h.

4. The method for preparing a high dielectric constant polyimide film according to claim 1, characterized in that: In step S2, the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, and 4,4'-bis(3-aminophenoxy)diphenyl sulfone is (1-3):(2-3):(4-5).

5. The method for preparing a high dielectric constant polyimide film according to claim 1, characterized in that: In step S3, the composite slurry includes the following raw materials: by weight, 15-30 parts BT@Al2O3, 1-5 parts modified boron nitride nanosheets, and 65-85 parts polyamic acid solution.

6. The method for preparing a high dielectric constant polyimide film according to claim 1, characterized in that: The method for preparing the modified boron nitride nanosheets is as follows: Step A: Adjust the pH of the Tris-HCl buffer solution to 8.5, add dopamine hydrochloride and mix well to obtain a dopamine solution; add boron nitride nanosheets to the dopamine solution, stir at 50-60℃ for 12-24h, and after filtration, washing and drying, obtain polydopamine-modified boron nitride nanosheets. Step B: Mix hydroxyl-terminated fluorinated vinyl polysiloxane, octamercaptopropyl-POSS, 2,2-dimethoxyphenylacetophenone and toluene evenly, react under 300-500W ultraviolet light for 10-20 min, and obtain fluorinated POSS after centrifugation, washing and drying; Step C: Polydopamine-modified boron nitride nanosheets are ultrasonically dispersed in toluene, fluorinated POSS is added, and the mixture is stirred at 60-70℃ for 10-14 hours. After filtration, washing, and drying, modified boron nitride nanosheets are obtained.

7. The method for preparing a high dielectric constant polyimide film according to claim 6, characterized in that: In step A, the concentration of Tris-HCl buffer is 0.01 mol / L, the concentration of dopamine solution is 3-5 g / L, and the mass of boron nitride nanosheets is 1-3% of the mass of Tris-HCl buffer.

8. The method for preparing a high dielectric constant polyimide film according to claim 6, characterized in that: The fluorinated POSS comprises the following raw materials: by weight, 5-10 parts of hydroxyl-terminated fluorinated vinyl polysiloxane, 1-5 parts of octamercaptopropyl-POSS, 0.1-0.5 parts of 2,2-dimethoxyphenylacetophenone, and 10-20 parts of toluene.

9. The method for preparing a high dielectric constant polyimide film according to claim 8, characterized in that: The preparation method of the hydroxyl-terminated fluorinated vinyl polysiloxane is as follows: Under nitrogen protection, octamethylcyclotetrasiloxane, pentamethylpentylcyclopentasiloxane and trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 100-110℃, tetramethylammonium hydroxide and deionized water are added and mixed evenly, and the reaction is carried out for 3-5 hours. The temperature is then raised to 145-150℃ and kept at that temperature for 2-3 hours. After filtration and drying, the hydroxyl-terminated fluorinated vinyl polysiloxane is obtained.

10. A polyimide film with high dielectric constant prepared by the preparation method according to any one of claims 1-9.